A phase IIA trial of acupuncture to reduce chemotherapy-induced peripheral neuropathy severity during neoadjuvant or adjuvant weekly paclitaxel chemotherapy in breast cancer patients. (September 2018) - Bao, Ting; Seidman, Andrew D.; Piulson, Lauren; Vertosick, Emily; Chen, Xi; Vickers, Andrew J.; Blinder, Victoria S.; Zhi, Wanqing I.; Li, Qing; Vahdat, Linda T.; Dickler, Maura N.; Robson, Mark E.; et al.
Abstract: Purpose: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and potentially dose-limiting side-effect of neurotoxic chemotherapy for cancer patients. We evaluated the preliminary efficacy of acupuncture in preventing worsening CIPN in patients receiving paclitaxel. Methods: In this phase IIA single-arm clinical trial, we screened stage I–III breast cancer patients receiving neoadjuvant/adjuvant weekly paclitaxel for development of CIPN. The primary objective was to assess acupuncture's efficacy in preventing the escalation of National Cancer Institute-Common Toxicity Criteria for Adverse Events (NCI-CTCAE), version 4.0, grade II CIPN to higher grades. Acupuncture was deemed worthy of further study if 23 or more of the 27 enrolled patients did not develop grade III CIPN. Outcome measures (NCI-CTCAE CIPN grade, Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity [FACT/GOG-Ntx], Neuropathic Pain Scale [NPS]) were obtained weekly during the intervention. Results: Of 104 patients screened, 37 developed grade II CIPN (36%), and 28 (27%) enrolled into the intervention phase; one was removed due to protocol violation. Of the 27 patients receiving acupuncture, 26 completed paclitaxel treatment without developing grade III CIPN, meeting our prespecified success criteria for declaring acupuncture worthy of further study. FACT/GOG-Ntx and NPS scores remained stable during the intervention while continuing weekly paclitaxel. Acupuncture treatment was well tolerated; 4 of 27 (15%) patients reported grade I bruising. Conclusions: Acupuncture was safe and showed preliminary evidence of effectiveness in reducing the incidence of high grade CIPN during chemotherapy. A follow-up randomised controlled trial is needed to establish definitive efficacy in CIPN prevention for patients at risk. Highlights: Thirty-six percent of screened patients developed grade II chemotherapy-induced peripheral neuropathy (CIPN). Only 1 of 27 patients in the intervention phase developed grade III CIPN. Only one patient developed grade III CIPN, so acupuncture was worthy of further study. Acupuncture was well tolerated, with 15% of patients reporting mild bruising.